Hey DJ, don't stop the music: Institutional work and record pooling practices in the United States' music industry. Issue 5 (4th July 2018) - Thompson, Neil
Abstract: Heeding calls to generate a creative synthesis between business history and organisation studies, this article analyses the emergence, institutionalisation and digitalisation of record pooling practices through the lens of institutional work. By developing an 'analytically structured history', this article contributes to the field of business history by demonstrating the value of practice and boundary work as organising categories. Practice and boundary work capture the continuous, recursive relations between structure and agency when constructing narrative explanations. It also contributes to neo-institutionalist history by demonstrating the embeddedness of institutional work – the everyday motivations and actions to revise practices and boundaries are shown to be intimately shaped by the conditions and affordances of historically-situated technologies.